A risk‐stratification model based on the initial concentration of the serum monoclonal protein and MYD88 mutation status identifies a subset of patients with IgM monoclonal gammopathy of undetermined significance at high risk of progression to Waldenström macroglobulinaemia or other lymphoproliferative disorders. (5th July 2019) - Varettoni, Marzia; Zibellini, Silvia; Boveri, Emanuela; Klersy, Catherine; Candido, Chiara; Rattotti, Sara; Ferretti, Virginia V.; Defrancesco, Irene; Mangiacavalli, Silvia; Nizzoli, Maria E.; Flospergher, Elena; Zerbi, Caterina; et al.
Summary: IgM monoclonal gammopathies of undetermined significance (IgM MGUS) are associated with a risk of progression to Waldenström macroglobulinaemia (WM) or other lymphoproliferative disorders (LPD) of 1–2% per year. We analysed 176 consecutive patients with IgM MGUS to evaluate risk factors for progression. With a median follow‐up of 83 months (1214 person‐years), 15 patients (8·5%) progressed to WM ( n = 14) or marginal zone lymphoma ( n = 1). The rate of progression was 1·32% per year (95% confidence interval [CI] 0·80–2·20). The serum monoclonal protein concentration and the MYD88 mutation were independent risk factors for progression (Hazard ratio [HR] 23·3, 95% CI 2·0–273·3, P = 0·012 and HR 24·4, 95% CI 2·2–275·3, P = 0·010, respectively). The cumulative incidence of progression, while considering death as a competing event, was 11·6% at 5 years and 38·0% at 10 years in MYD88 ‐mutated patients with a serum monoclonal protein of 10 g/l or higher, as compared with 0% at 5 years and 1·1% at 10 years for patients with none or one risk factor. This risk‐stratification model is able to identify a subset of patients with IgM MGUS at high risk of progression to WM or LPD who deserve a lifelong follow‐up.